Cliticization as Extraction: The Big DP Hypothesis Revisited - Cardinaletti, Anna (Revista da Associação Portuguesa de Linguística, 2019)
In this paper, it is argued that cliticization is extraction out of a big DP. Big DPs contain both clitic pronouns and associate DP arguments (Torrego, 1995; Uriagereka, 1995, 2005, among others). The DP can be pronounced, which gives rise to a clitic doubling configuration, or can be null, in which case a simple clitic configuration is obtained. This hypothesis allows us to explain not only the limited movement possibilities of clitic pronouns (cf. Belletti 1999), but also their restricted inventory: Not all complements can be cliticized. If clitic pronouns are reduced maximal projections (Cardinaletti and Starke, 1999), the big DP hypothesis needs to be revisited. Clitic pronouns cannot be assumed to be the heads of big DPs, as was suggested in the abovementioned proposals. The proposal is that clitic pronouns are merged as specifiers of the highest projection of big DPs, namely K(ase)P, which also captures the fact that they are the only elements which bear morphological case in languages like Italian.